A bamboo-derived cellulose “high-speed rail” scaffold with gradient topology and temporal immunomodulation for tendon–bone interface regeneration - Yixuan Huang; Chen Chen; Hai Lan; Yichao Liu; Likun Liu; Heng Zhu; Lei Wang; Chenjian Peng; Hao Shu; Jiazhi Yang; Xin Liu; Luning Sun (Carbohydrate Polymers, 2026)

Enhancing performance and mitigating membrane fouling in an ICAMBR through poly aluminum chloride addition - Yumeng Yan; Zhenhao Wang; Luning Tian; Yang Liu; Min Xia; Yi Han; Shichan Qin; Feixiang Zan; Juan Mao; Xiaohui Wu; Xiejuan Lu (Journal of Environmental Chemical Engineering, 2026)

A multifunctional soft microrobot for untethered targeted delivery and temperature mapping - Zhihao Qin; Xinrui Shi; Ling Zhu; Luning Zhao; Meixin Le; Wanqi Jia; Yunhao Tai; Guangli Liu; Tingting Luo; Runhuai Yang (Chemical Engineering Journal, 2026)

Sustainability of corrosion-induced degradation of marine engineering structures: A bibliometric analysis based on CiteSpace and VOSviewer (1972-2026) - Zihan Yang; Guangda Yu; Chengyong Li; Bingxuan Zhao; Yansong Liu; Guoqiang Tang; Weihang Yu; Qianhua Liu; Luning Liu; Yu Sun; Yuxin Shi; Zining Li; et al. (Marine Environmental Research, 2026)

A Genome-Wide Association Study Identifies Novel Genetic Variants Associated with Knee Pain in the UK Biobank (n = 439,743) - Yiwen Tao; Qi Pan; Tengda Cai; Luning Yang; Mainul Haque; Tania Dottorini; Weihua Meng (Phenomics, 2026)

Biodegradable film combined with ploughing: An approach to improve the sustainability of rainfed spring maize production - Rui Qian; Luning Du; Wenjing Li; Wei Wang; Yang Zhang; Yujie Gao; Wenjing Feng; Jiaji Ding; Wenbo Lv; Pengyao Qin; Tie Cai; Xiaolong Ren; et al. (Soil and Tillage Research, 2025)

Spatiotemporal Differences in Tectonic Deformation and Its Dynamic Mechanisms in the East China Sea Shelf Basin - Junlan Song; Yumao Pang; Chuansheng Yang; Yanqiu Yang; Luning Shang; Changqing Yang; Jing Sun (Journal of Ocean University of China, 2025)

Impact of phosphorus on the transfer of extracellular antibiotic resistance genes in water-sediment systems - Di Zhang; Jingxuan Liang; Yu Wang; Chao Xing; Yuzi Song; Ce Wang; Zikuo Liu; Xiaobin Yang; Luning Gong; Huijuan Shi; Zhao Zhao (Journal of Environmental Chemical Engineering, 2025)

Differences in Mesozoic–Cenozoic Structural Deformation Between the Northern and Southern Parts of the East China Sea Shelf Basin and Their Dynamic Mechanisms - Chuansheng Yang; Junlan Song; Yanqiu Yang; Luning Shang; Jing Liao; Yamei Zhou (Journal of Marine Science and Engineering, 2025)
The East China Sea Shelf Basin (ECSSB) and its adjacent areas, as key regions of the ocean–continent transition zone, have been affected by multiple complex plate collisions, subduction, and back-arc tension since the Mesozoic Era. The structural deformation provides a large amount of geological information on the ocean–continent transition zone. There are significant spatiotemporal differences in the structural deformation within the basin. However, the research remains insufficient and understanding is inconsistent, especially regarding the systematic study of the differences and dynamic mechanisms of north–south structural deformation, which is relatively lacking. This study is based on two-dimensional multi-channel deep reflection seismic profiles spanning the southern and northern basin. Through an integrated re-analysis of gravity, magnetic, and OBS data, the deformation characteristics and processes of the Meso-Cenozoic structures in the basin are analyzed. The differences in structural deformation between the southern and northern basin are summarized, and the controlling effects of deep crust–mantle activity and the influencing factors of shallow structural deformation are explored. Based on deep reflection seismic profiles, the structural deformation characteristics of the Yushan–Kume fault are revealed for the first time, and it is proposed that NW faults, represented by the Yushan–Kume fault, have important tuning effects on the north–south structural differential deformation in the ECSSB. The thermal subsidence of the lithosphere is the direct cause of the development of the Mesozoic ECSSB, while the subduction of the Paleo-Pacific plate is one of the important factors contributing to it. The combined effect of the two has led to significant differences between the northern and southern Mesozoic basin. During the Cenozoic Era, the alternating subduction and changes in the direction of subduction of the Pacific Plate led to spatiotemporal differences in structural deformation within the ECSSB. The development of NW faults was a key factor in the differences in structural deformation between the northern and southern basin. The study of structural deformation differences in the ECSSB not only deepens our understanding of the tectonic evolution in the East Asian continental margin region, but also has important significance for the exploration and evaluation of deep hydrocarbon resources in the ECSSB.

Intraoceanic active rifting revealed by deep seismic reflection imaging in the southern Bay of Bengal, northeastern Indian Ocean - Luning Shang; Gang Hu; Thomas P. Ferrand; Jun Pan; Chuansheng Yang (Earth and Planetary Science Letters, 2025)

Toxicity of rare earth elements europium and samarium on zebrafish development and locomotor performance - Boyu Yang; Luning Sun; Zheng Peng; Qing Zhang; Mei Lin; Zhilin Peng; Jue Yang; Lan Zheng (Journal of Hazardous Materials, 2025)

Enhancing H2O2 synthesis in photocatalytic self-Fenton degradation of antibiotics by modulating surface hydrophobicity of Fe-doped g-C3N4 with ionic liquids - Hongjie Zhu; Yushuo Sui; Zirui Yao; Haitao Zhao; Minghui Li; Luning Zou; Yikai Yang; Hongguo Hao; Pengfang Zhang; Hui-Juan Wang; Yao-Yao Wang; Shirong Kang (Journal of Environmental Chemical Engineering, 2025)

Refining the final phase of the seafloor spreading process in the West Philippine Basin through the recalibration of magnetic isochrones - Luning Shang; Hailong Li; Kai Lu; Panfeng Li; Gang Hu; Yong Zhang; Yongjian Yao; Chuansheng Yang (Tectonophysics, 2024)

Biofouling recognition and boundary tracking control for underwater cleaning robots - Hang Su; Siyue Liu; Luning Zhang; Yanhu Chen; Canjun Yang (Ocean Engineering, 2024)

Review of underwater adsorptive-operating robots: Design and application - Canjun Yang; Siyue Liu; Hang Su; Luning Zhang; Qingchao Xia; Yanhu Chen (Ocean Engineering, 2024)

Induced seismicity in the Changning salt mining zone, China, could be driven by the pore-pressure diffusion - Haozhe Yang; Rumeng Guo; Guang Zhai; Jiangcun Zhou; Kun Dai; Yong Zheng; Luning Li; Heping Sun (Tectonophysics, 2024)

Speciation and gas-liquid equilibrium study of CO2 absorption in aqueous MEA-DEEA blends - Rui Zhang; Haonan Liu; Ruixi Liu; Yingjie Niu; Luning Yang; Francesco Barzagli; Chao'en Li; Min Xiao (Gas Science and Engineering, 2023)

The association between long-term exposure to outdoor artificial light at night and poor sleep quality among Chinese veterans: A multi-city study - Xinyi Sun; Jiping Tan; Yan Chen; Yuewei Liu; Guang-Hui Dong; Bo-Yi Yang; Nan Li; Luning Wang; Shanshan Li; Gongbo Chen; Yuming Guo (International Journal of Hygiene and Environmental Health, 2023)

Origin of the southern Ryukyu Forearc Terrace: A seaward-protrusion of arc crust elevated by subducted asperities? - Luning Shang; Gang Hu; Yongtao Chen; Chuansheng Yang; Yong Zhang (Journal of Asian Earth Sciences, 2023)

Performance study of energy conversion system for ocean thermal profiler - Yanhu Chen; Bingzhe Chen; Meiling He; Luning Zhang; Qingchao Xia; Canjun Yang (Frontiers in Marine Science, 2022)
With the increasing scarcity of energy in the world, energy has become an important part of restricting the development and application of traditional ocean profilers. The method of converting ocean thermal energy (OTE) into electrical energy through an energy conversion system is a solution. The model establishment and performance analysis of the energy conversion system are the basis of the ocean thermal profiler (OTP) design. The model and performance are affected by the coupling of multiple parameters, especially rotational speed and pressure. In this study, a universal parameterized model for multi-parameter coupling was proposed. System performance analysis based on experiments including load current, speed, mechanical efficiency and total efficiency was presented. After model parameter identification, the error of mechanical efficiency was within 5%; the total efficiency error was less than 12.8%, and the maximum efficiency point error didn’t exceed 2.21%. The results indicated that the parameterized model was satisfactory for the engineering applications and could guide the design of OTP.

Correction to: Risk exposure assessment of per- and polyfluoroalkyl substances (PFASs) in drinking water and atmosphere in central eastern China - Zhibo Lu; Rong Lu; Hongyuan Zheng; Jing Yan; Luning Song; Juan Wang; Haizhen Yang; Minghong Cai (Environmental Science and Pollution Research, 2018)

Risk exposure assessment of per- and polyfluoroalkyl substances (PFASs) in drinking water and atmosphere in central eastern China - Zhibo Lu; Rong Lu; Hongyuan Zheng; Jing Yan; Luning Song; Juan Wang; Haizhen Yang; Minghong Cai (Environmental Science and Pollution Research, 2018)

New magnetic data of the southern East China Sea and some geological interpretations - Luning Shang; Xunhua Zhang; Runlin Du; Yonggang Jia; Zhenxing Tian; Bo Han; Chuansheng Yang (Studia Geophysica et Geodaetica, 2016)

Kinetics of the aerobic co-metabolism of 1,1-dichloroethylene by Achromobacter sp.: a novel benzene-grown culture - Shizong Wang; Qi Yang; Luning Zhang; Yeyao Wang (Biotechnology Letters, 2014)